Measurements of a Multi Feed Reflector Antenna for SAR Systems Based on Digital Beam Forming - Tienda Herrero, Carolina; Patyuchenko, Anton; Gabler, Bernd; Limbach, Markus; Krieger, Gerhard (ESA Antenna Workshop, 2013)
In the last years, the Synthetic Aperture Radar (SAR) systems evolution migrates toward the use of multi-channel systems based on Digital Beam Forming (DBF) techniques [1]. This tendendy allows fulfilling stringent SAR requirements, providing high spatial resolution within a wide swath. Moreover, the combination of DBF techniques with parabolic reflector antennas merges both flexibility and high antenna gain ending up in a high versatile system [2]. One of the main parts in a Digital Beam Forming (DBF) Synthetic Aperture Radar system is constituted by the antenna. An accurate characterization of the antenna radiation pattern is of high interest for the calibration of the system which guarantees the performance and versatility of the DBF network. This paper describes the measurements of a multi- feed single offset reflector antenna designed in X-band. The antenna is part of an on ground multi-channel radar system used to demonstrate ind investigate DBF techniques at HR/DLR
DLR Import::2019-04-03